Teaching Methods, Personality Types, and Reading Comprehension - Andhi Dwi Nugroho (Journal of English Education, Literature and Linguistics, 2019)
The primary aim of this study is to provide the empirical and theoritical evidence for the effect of teaching methods and personality types on reading comprehension. This quassi experimental study involved 100 students under investigation, which were determined randomly through multistage random sampling technique. The results of the research indicate that there is an interaction effect between the teaching methods and personality types on the reading comprehension; there is no significant difference in the reading comprehension between the group of students who learn using Cooperative Integrated Reading and Composition (CIRC) and those who learn using Problem Based Instruction (PBI); the students’ reading comprehension having extrovert personality is better than those having introvert personality; the students’ reading comprehension having extrovert personality who learn using CIRC is higher than those who learn using PBI; and the students’ reading comprehension having introvert personality who learn using the CIRC is lower than those who learn using PBI.